2016
DOI: 10.5152/iao.2016.2338
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cVEMP and ABR for the Evaluation of Vestibular Migraine

Abstract: In this study, we aimed to determine the characteristics of the cVEMP and ABR responses of patients with VM and migraine in contrast to healthy controls. In this study, cVEMP and ABR changes during the VM attack period were compared with the cVEMP and OBJECTIVE: Vestibular migraine (VM) is a clinical condition characterized by temporal overlap between vestibular symptoms and migraine. In this study, we aimed to determine the changes in vestibular myogenic potential (cVEMP) and auditory brainstem response (ABR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…In a longitudinal study by Sand et al (4), the intensity dependence of BAEP in migraine may not be a passive response to brainstem dysfunction. There were no changes in BAEP before the onset of migraine, and the peak latency of I-V wave and the peak latency of III-V wave increased after the onset of headache; the changes in BAEP seemed to reflect the slight effect of migraine symptoms on the serotonin brain stem pathway (27,28). In this study, patients in the migraine group had a longer V wave latency period than those in the control group.…”
Section: Discussioncontrasting
confidence: 50%
“…In a longitudinal study by Sand et al (4), the intensity dependence of BAEP in migraine may not be a passive response to brainstem dysfunction. There were no changes in BAEP before the onset of migraine, and the peak latency of I-V wave and the peak latency of III-V wave increased after the onset of headache; the changes in BAEP seemed to reflect the slight effect of migraine symptoms on the serotonin brain stem pathway (27,28). In this study, patients in the migraine group had a longer V wave latency period than those in the control group.…”
Section: Discussioncontrasting
confidence: 50%
“…Bayazit et al [2001] found that 35% of the studied migraine cases had abnormal ABR, with elongation in the absolute wave latencies or elongation in both wave latencies and IPL. In the study by Sürmeli et al [2016], the authors observed that the wave V peak latency was prolonged significantly in the group of VM. In our study, we observed prolonged wave V latency and I-V IPL in the migraine group and prolonged I-V IPL in the VM group.…”
Section: Discussionmentioning
confidence: 95%
“…Our cVEMP and oVEMP findings were not correlated to any clinical symptom, except that cVEMP amplitude was statistically significant larger in both ears of migraine patients with aura compared to those without aura. However, Sürmeli et al [22] found that the cVEMP P13-N23 amplitudes in migraine patients with aura were significantly smaller than in patients without aura. In their χ 2 = 0.037, p = 1.000 †All migraine cases with abnormal cVEMP (n = 7) had delayed latency, even though they all had symmetrical amplitude.…”
Section: Discussionmentioning
confidence: 97%